Catalytic studies of Boron-HZSM-5 zeolite for methane conversion to higher hydrocarbons - Mat, Ramli (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
The direct conversion of methane to liquid hydrocarbons either over metal catalyst or zeolite is so far not successful in achieving the methane conversion and liquid hydrocarbons selectivity within the economic range due to oxidation of the product. The present research concern the modification of HZSM-5 catalyst with boron in order to reduce the acidity of the catalyst and thus reduce it oxidation activity. A series of boron was loaded into HZSM-5 zeolite via impregnation. Catalyst characterization was carried out using XRD and TPD. The catalytic activity for methane conversion depends on the boron loading. A higher loading ofboron on HZSM-5 result in lower activity for methane conversion.